Self-Compassion and Psychological Well-Being among NonLocal Students: The Mediating Role of Resilience - Maris, Wihelmina Yubilia; Fathiyah, Kartika Nur (Journal of Educational, Health and Community Psychology, 2024)
Psychological well-being is one of the most essential aspects of the life of overseas students. To improve psychological well-being, students should have a positive attitude towards themselves and good resilience with the aim that they can live a life with good mental health and well-being. Therefore, this research aims to determine the role of resilience in the relationship between self-compassion and psychological well-being among non-local students in Indonesia. The study used the Psychological Well-Being Scale (PWBS-18), the Indonesian Version of the Self-Compassion Scale, and the Nicholson McBride Resilience Questionnaire (NMRQ) on 142 non-local students. The results prove that resilience partially mediates the relationship between self-compassion and psychological well-being. It indicates that increasing resilience leads to an increase in self-compassion and it affects the development of psychological well-being. Non-local students who love themselves and accept their weaknesses and failures tend to be able to cope with stress and survive in every difficult condition experienced in their lives, which will lead them to reduce psychological distress.